Finding one's way : how mentoring can lead to dynamic leadership - Crow, Gary Monroe, 1947- 4 0 16; 1950- Matthews, L. Joseph; 5 (Thousand Oaks, California : Corwin Press, 1998)
Discusses the benefits of mentoring in education, discussing planning, mentor selection, training, and evaluation.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Training of;Training. -- Mentoring in education;School principals;Educational leadership;School superintendents and principals;Leadership. -- United States.;United States.;United States.;United States; 20; 2